2006
DOI: 10.1266/ggs.81.355
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of two anther-specific genes encoding putative RNA-binding proteins, AtRBP45s, in Arabidopsis thaliana

Abstract: RRM (RNA-recognition motif) domain is important for the post-transcriptional regulation of gene expression including RNA processing. In our previous study, we found one anther-and/or pollen-specific gene ( LjRRM1 , previously named as LjMfb-U93 ) in model legume, Lotus japonicus . Because of the richness of genomic information of another model plant, Arabidopsis thaliana , for functional analysis, we identified and characterized the orthologous genes in A. thaliana . By comparison of the partial nucleotide seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…4), consistent with earlier reports (Lorkovic et al, 2000;Park et al, 2006). Since this gene also was induced in response to oxidative stress, we speculate it may be crucial for coordinating the adaptive response of plants to stresses in different organs and different developmental stages.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4), consistent with earlier reports (Lorkovic et al, 2000;Park et al, 2006). Since this gene also was induced in response to oxidative stress, we speculate it may be crucial for coordinating the adaptive response of plants to stresses in different organs and different developmental stages.…”
Section: Discussionsupporting
confidence: 91%
“…RBPs with triple RRMs have been implicated in various facets of RNA metabolism, including RNA stability and splicing, and show similarities to some metazoan hnRNPs (Lorkovic and Barta, 2002). These proteins were also shown to be involved in flower development (Park et al, 2006;Schomburg et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Honys et al (2000) have shown that the pollen‐specific ntp303 transcript is translationally repressed. Park et al (2006) have suggested that anther‐ and pollen‐specific RNA‐recognition motif (RRM) domain proteins may play a role in translational repression. However, this simply pushes back the question further – what regulates such regulators at this phase of development?…”
Section: Alternation and Gametophyte Development In Angiospermsmentioning
confidence: 99%
“…Few putative RNA-binding proteins have been characterized in detail in mature pollen in any species (Park et al, 2006), and to our knowledge, none have been phenotypically associated with aberrant progamic development. However, a number of conserved sequence elements in transcript UTRs with potential or proven roles in influencing mRNA translation or stability have been identified (Hulzink et al, 2003), most notably in the tobacco ntp303 transcript (Hulzink et al, 2002).…”
Section: Discussionmentioning
confidence: 95%